Evaluation of gene expression of three adrenergic receptors in infertile women with poor ovarian response, candidate for IVF - Farideh Zafari Zangeneh (Tehran University Medical Journal, 2020)
Background: Most studies show that 9 to 24% of people who are in in vitro fertilization (IVF) cycles are women who respond poorly to ovarian stimulation. Women with poor ovarian response (POR) are a group of infertile patients whose ovarian reserve, ovarian response to medication, and the quality of ovum are declining. Therefore, the number of female cycles, the number of fetuses from the oocyte and the rate of pregnancy in these women is reduced. The purpose of this study was to investigate the expression of three adrenoceptor receptor genes in the cumulus cells of women with poor ovarian response in culture medium. Methods: This case-control study was conducted in two groups: study (POR) and control (oocyte donor's women) groups. POR diagnosis was performed by ESHRE Bologna criteria. After puncture of the follicles, cumulus-oocyte complex was collected and the cumulus cells (CCs) were isolated by enzyme and are counted with Neobar lamella and then were added in the culture medium. After completing the culture, RNA was extracted from cumulus cells and the RNA concentration was read by the Spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA). Then cDNA synthesized and primers designed for ADR-α1, 2 and ADR-B2 or gene expression by real-time polymerase chain reaction (PCR) technique. The research was done in Reproductive Health Research Center of Imam Khomeini Hospital, Tehran University of Medical Sciences, Tehran, Iran, from April to December 2017. Results: Comparison of the results of ADR-α1, 2 gene expressions in cumulus cells showed a significant decrease, but ADR-B2 was not significant in two groups. Correlation coefficients also showed that there are relationship between three adrenoceptors and their effects on each other. Conclusion: Our results showed that the decreased expressions of ADR-α1, 2 probably related to activation of the sympathetic system and release of the more neurotransmitter that lead to down-regulation of ADR-α1, 2 in the cell membrane of cumulus in culture medium.